Context-Responsive Leadership: Examining Superintendent Leadership in Context. - Paul V. Bredeson; Hans W. Klar; Olof Johansson (Arizona State University, 2011)
It is widely acknowledged that context matters, that it affects leadership practices. A large body of descriptive studies documents common elements in the work of school superintendents. What is less well known is how superintendents leadership may be expressed very differently given the varying contexts in which they work. The purpose of this cross-national study was to identify the specific variations in context which influence superintendents leadership, and to examine how superintendents respond to these variations in context. Structured, in-depth interviews were conducted with 12 superintendents- six from across Sweden and six from Wisconsin, in the United States. The findings illustrate that the work of superintendents is paradoxically similar but different. Superintendents described common primary work priorities, challenges and contextual variations which influenced their practice. Yet, differences in district size, organizational culture, community characteristics, and geographic location significantly influenced their leadership practices. Despite their challenges, all superintendents responded to and shaped the context of their work. The study provides illustrative examples of superintendent leadership in situ, and supports the argument that leadership is both embedded in and influenced by context. The study also furthers the authors emerging theory of context-responsive leadership.